Time-dependent condensate fraction in an analytical model - Simon, Alessandro; Wolschin, Georg (Physica. A, Statistical mechanics and its applications, 2021)
We apply analytical solutions of a nonlinear boson diffusion equation (NBDE) that include boundary conditions at the singularity to calculate the time evolution of the entropy during evaporative cooling of ultracold atoms, and the time-dependent condensate fraction. For suitable initial conditions it is found to agree with available data on 23Na.
Gesehen am 15.06.2021